2022
DOI: 10.1038/s41368-022-00193-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of osteoclastogenesis reveals the pathogenesis and therapeutics of bone loss under sympathetic neurostress

Abstract: Sympathetic cues via the adrenergic signaling critically regulate bone homeostasis and contribute to neurostress-induced bone loss, but the mechanisms and therapeutics remain incompletely elucidated. Here, we reveal an osteoclastogenesis-centered functionally important osteopenic pathogenesis under sympatho-adrenergic activation with characterized microRNA response and efficient therapeutics. We discovered that osteoclastic miR-21 was tightly regulated by sympatho-adrenergic cues downstream the β2-adrenergic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“… 39 Among the ADRs that respond to sympathoexcitation, ADRBs are thought to play a crucial role in mediating the effects of sympathetic outflow across the organism, particularly in relation to bone, which has become a focal point of research attention. 36 Moreover, it has been verified that bone development, remodeling and regeneration depend on microenvironmental factors, 48 among which vascular endothelium transports oxygen and nutrients as well as carries away waste products. 36 Specifically, type H vessels are located at the distal end of the bone arterial network, creating a metabolically active microenvironment that has privileged access to oxygen, nutrients, and growth factors released by ECs, maintaining perivascular osteoprogenitors, contributing to bone vasculature growth and coupling angiogenesis with osteogenesis, ultimately promoting the bone generation and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Among the ADRs that respond to sympathoexcitation, ADRBs are thought to play a crucial role in mediating the effects of sympathetic outflow across the organism, particularly in relation to bone, which has become a focal point of research attention. 36 Moreover, it has been verified that bone development, remodeling and regeneration depend on microenvironmental factors, 48 among which vascular endothelium transports oxygen and nutrients as well as carries away waste products. 36 Specifically, type H vessels are located at the distal end of the bone arterial network, creating a metabolically active microenvironment that has privileged access to oxygen, nutrients, and growth factors released by ECs, maintaining perivascular osteoprogenitors, contributing to bone vasculature growth and coupling angiogenesis with osteogenesis, ultimately promoting the bone generation and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a sensitive yet stable stress indicator with direct functional associations is in demand to be established. Notably, considering chronic stress, complex stressors often depends on complicated yet dynamic factors which may influence the outcomes, such as the frequency, durability and strength of stressors ( Hu et al 2022 ; Sui et al 2022 ), thus acute stress might be more suitable and convenient to support this pioneering work with EV biomarkers in psychological stress. However, it will still be necessary to verify or compare the EV biomarker in chronic stress in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 36 found that osteoclastogenesis crucially contributed to sympathoadrenergic regulation of the bone. Another animal experiment 37 specifically knocked out tyrosine hydroxylase in a mouse line and found that catecholamines delayed fracture healing by increasing the number of inflammatory cells.…”
Section: Ar Blockersmentioning
confidence: 92%